Monitoring of gene expression in tacrolimus‐treated de novo renal allograft recipients facilitates individualized immunosuppression: Results of the IMAGEN study. Issue 10 (31st March 2021) - Sommerer, Claudia; Brunet, Mercè; Budde, Klemens; Millán, Olga; Guirado Perich, Lluis; Glander, Petra; Meuer, Stefan; Zeier, Martin; Giese, Thomas
Abstract : Aims: Calcineurin inhibitors (CNI) have a small therapeutic window, and drug monitoring is required. Pharmacokinetic monitoring does not correlate sufficiently with clinical outcome. Therefore, the expression of nuclear factor of activated T cells (NFAT)‐regulated genes in the peripheral blood has been suggested as a potentially useful immune monitoring tool to optimize CNI therapy. NFAT‐regulated gene expression (RGE) was evaluated in renal allograft recipients as predictive biomarker to detect patients at risk of acute rejection or infections. Methods: NFAT‐RGE (interleukin‐2, interferon‐γ, granular‐macrophage colony‐stimulating factor) was evaluated by quantitative real‐time polymerase chain reaction in whole blood samples at day 7, day 14, month 1, 3, and 6 after transplantation in 64 de novo renal allograft recipients from 3 European centres. Immunosuppression consisted of tacrolimus (Tac), mycophenolic acid, and corticosteroids. Results: Tac concentrations (C0 and C1.5) correlated inversely with NFAT‐RGE ( P <  .01). NFAT‐RGE showed a high interindividual variability (1–61%). Patients with high residual gene expression (NFAT‐RGE ≥30%) were at the increased risk of acute rejection in the following months (35 vs . 5%, P =  .02), whereas patients with low residual gene expression (NFAT‐RGE <30%) showed a higher incidence of viral complications, especially cytomegalovirus and BK virus replication (52.5 vs . 10%, P =  .01). Conclusions: NFAT‐RGE was confirmed as a potential noninvasive early predictive biomarker in the immediate post‐transplant period to detect patients at risk of acute rejection and infectious complications in Tac‐treated renal allograft recipients. Monitoring of NFAT‐RGE may provide additional useful information for physicians to achieve individualized Tac treatment.